The UK Cardiac and Vascular Surgery Interventional Anaemia Response (CAVIAR) Study: protocol for an observational cohort study to determine the impact and effect of preoperative anaemia management in cardiac and vascular surgical patients. Issue 4 (18th April 2017) - Chau, Marisa; Richards, Toby; Evans, Caroline; Butcher, Anna; Collier, Timothy; Klein, Andrew
Abstract : Introduction: Preoperative anaemia is linked to poor postsurgical outcome, longer hospital stays, greater risk of complications and mortality. Currently in the UK, some sites have developed anaemia clinics or pathways that use intravenous iron to correct iron deficiency anaemia prior to surgery as their standard of care. Although intravenous iron has been observed to be effective in a variety of patient settings, there is insufficient evidence in its use in cardiac and vascular patients. The aim of this study is to observe the impact and effect of anaemia and its management in patients undergoing cardiac and vascular surgery. In addition, the UK Cardiac and Vascular Surgery Interventional Anaemia Response (CAVIAR) Study is also a feasibility study with the aim to establish anaemia management pathways in the preoperative setting to inform the design of future randomised controlled trials. Methods and analysis: The UK CAVIAR Study is a multicentre, stepped, observational study, in patients awaiting major cardiac or vascular surgery. We will be examining different haematological variables (especially hepcidin), functional capacity and patient outcome. Patients will be compared based on their anaemia status, whether they received intravenous iron in accordance to their hospital's preoperative pathway, and their disease group. The primary outcomes are the change in haemoglobin levels from baseline (before treatment) to before surgery; and the number of successful patients recruited and consented (feasibility). The secondary outcomes will include changes in biomarkers of iron deficiency, length of stay, quality of life and postoperative recovery. Ethics and dissemination: The study protocol was approved by the London-Westminster Research Ethics Committee (15/LO/1569, 27 November 2015). NHS approval was also obtained with each hospital trust. The findings of the study will be published in peer-reviewed journals. Trial registration number: Clinical Trials registry (NCT02637102 ) and the ISRCTN registry (ISRCTN55032357 ).